Major carotenoid composition of Brazilian Valencia orange juice: Identification and quantification by HPLC - Gama, JJT; Sylos, Célia Maria de [UNESP] (Elsevier B.V., 2005)
The carotenoid composition of Brazilian Valencia orange juice was determined by open column chromatography (OCC) and high-performance liquid chromatography. Carotenoid pigments were extracted using acetone and saponified using 10% methanolic potassium hydroxide. Sixteen pigments were isolated by OCC and identified as alpha-carotene, zeta-carotene, beta-carotene, alpha-cryptoxanthin, beta-cryptoxanthin, lutein-5,6-epoxide, violaxanthin, lutein, antheraxanthin, zeaxanthin, luteoxanthin A, luteoxanthin B, mutatoxanthin A, mutatoxanthin B, auroxanthin B and trollichrome B. Thirteen carotenoid pigments were separated using a ternary gradient (acetonitrile-methanol-ethyl acetate) elution on a C-18 reversed-phase column. Among these, violaxanthin, lutein, zeaxanthin, beta-cryptoxanthin, zeta-carotene, alpha-carotene, and beta-carotene were quantified. The total carotenoid content was 12 +/- 6.7 mg/1, and the major carotenoids were lutein (23%), beta-cryptoxanthin (21%), and zeaxanthin (20%). 2005 Elsevier Ltd. All rights reserved.
Keywords: carotenoid composition; orange juice; quantification; HPLC; citrus; open column chromatography